Bisphenol A exposure in myasthenia gravis: Potential targets and mechanisms revealed by network toxicology and molecular dynamics - Shupeng Wu; Yaoqi Wu; Li Zhang; Jun Zhu (PLoS ONE, 2026)
Background Myasthenia gravis (MG) is a B-cell-mediated autoimmune disease characterized by impaired neuromuscular transmission. Although genetic predisposition and thymic abnormalities are well recognized, they cannot fully explain the increasing incidence and regional heterogeneity of MG, highlighting the potential contribution of environmental factors. Bisphenol A (BPA), a ubiquitous endocrine-disrupting chemical, exhibits estrogenic activity, immunomodulatory effects, and mitochondrial toxicity, and has been implicated in multiple autoimmune disorders. However, the potential role of BPA in MG pathogenesis remains largely unexplored. Methods BPA-related targets and MG-associated genes were collected from public databases, and overlapping targets were identified. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were performed to explore the biological functions and pathways of the overlapping targets. Candidate targets were screened using four machine-learning algorithms, including least absolute shrinkage and selection operator (LASSO) regression, support vector machine-recursive feature elimination (SVM-RFE), random forest (RF), and extreme gradient boosting (XGBoost). Differential expression and diagnostic performance were validated using the Gene Expression Omnibus (GEO) dataset GSE85452. Immune infiltration was assessed using CIBERSORT. Molecular docking and molecular dynamics (MD) simulations were conducted to evaluate the potential binding stability and interaction modes between BPA and key target proteins. In addition, C2C12 myoblasts were treated with different concentrations of BPA for 24 h, and cell viability was assessed using the Cell Counting Kit-8 (CCK-8) assay. Based on the cell viability results, 50 μM BPA was selected for quantitative reverse transcription polymerase chain reaction (qRT-PCR) and Western blot analyses of key genes. Results A total of 225 overlapping targets were identified between BPA exposure-related targets and MG-associated genes. Enrichment analyses showed that these targets were mainly associated with ion transport, membrane potential regulation, muscle system processes, immune signaling, apoptosis, endocrine resistance, and AGE–RAGE signaling pathways.Four machine-learning algorithms identified cholinergic receptor nicotinic beta 1 subunit (CHRNB1), KRAS proto-oncogene, GTPase (KRAS), phosphomannomutase 2 (PMM2), and toll-like receptor 4 (TLR4) as candidate targets. Validation in the GSE85452 dataset showed that CHRNB1, PMM2, and TLR4 were significantly upregulated in MG samples compared with control samples, whereas KRAS showed no significant difference. receiver operating characteristic (ROC) analysis further demonstrated that CHRNB1, PMM2, and TLR4 had good diagnostic performance, with area under the ROC curve (AUC) values of 0.827, 0.856, and 0.821,respectively. Immune infiltration analysis revealed altered immune cell infiltration patterns and associations between key targets and specific immune cell subsets. Molecular docking predicted favorable binding of BPA to CHRNB1, PMM2, and TLR4, with binding energies of −7.4, −5.7, and −5.8 kcal/mol, respectively. MD simulations further supported the potential stability of these BPA-target complexes. In vitro experiments showed that BPA reduced C2C12 cell viability in a concentration-dependent manner. qRT-PCR validation showed that treatment with 50 μM BPA significantly upregulated Chrnb1 expression, while downregulating Pmm2 and Tlr4 expression.Western blot analysis further confirmed that BPA exposure significantly decreased the protein expression of TLR4 and PMM2, while increasing that of CHRNB1 in C2C12 cells. Conclusions This study provides integrated computational and experimental evidence that BPA exposure may be associated with MG-related molecular alterations. BPA may affect MG-related biological processes through the regulation of ion transport, neuromuscular signaling, immune activation, and glycosylation-related metabolism. CHRNB1, PMM2, and TLR4 may serve as potential molecular links between BPA exposure and MG-related pathological processes.